Annealing High Aspect Ratio Microgels into Macroporous 3D Scaffolds Allows for Higher Porosities and Effective Cell Migration (Adv. Healthcare Mater. 24/2022). Issue 24 (21st December 2022) - Suturin, Alisa C.; Krüger, Andreas J. D.; Neidig, Kathrin; Klos, Nina; Dolfen, Nina; Bund, Michelle; Gronemann, Till; Sebers, Rebecca; Manukanc, Anna; Yazdani, Ghazaleh; Kittel, Yonca; Rommel, Dirk; et al.
Abstract : Macroporous Scaffolds In article 2200989 by Laura De Laporte and co‐workers, rod‐shaped microgels with high aspect ratios (5–20) are produced via in‐mold copolymerization of polyethylene glycol diacrylate and 2‐aminoethylmethacrylate, and subsequently annealed into macroporous scaffolds using an epoxy‐functionalized interlinking agent. The higher microgel aspect ratios lead to porosities up to 90% and mean pore sizes up to 82 µm, while supporting rapid, extensive filling of the constructs by fibroblasts.